Formula Optimization of o/w Cream Combination Oxybenzone and Titanium Dioxide and Its In Vivo Activity Testing - Ribka Elcistia; Abdul Karim Zulkarnain (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
The downside effects from sunlight exposure can be reduced by using sunscreen. Emulsifier optimization of triethanolamine (TEA) stearate and cetyl alcohol in sunscreen cream containing combination of oxybenzone and titanium dioxide is expected to produce the desired cream optimum formula with good physical stability. This study aimed to determine the optimum TEA sterate and cetyl alcohol proportion and figure out the SPF value of o/w cream containing combination of oxybenzone and titanium dioxide. The optimum formula was obtained based on cream physical characteristics testing with Simplex Lattice Design method using software Design Expert version 9.0.4. One sample t-test was used to determine the difference of optimum formula value between research and software Design Expert version 9.0.4 analysis. The comparison between optimum formula o/w cream combination oxybenzone and titanium dioxide during 4 weeks storage was analyzed using ANOVA test. The SPF value testing through in vivo was conducted against female rabbits strain New Zealand White induced by 8-methoxyprosalen. The result showed that proportion TEA stearate and cetyl alcohol which produced the optimum formula of o/w cream combination oxybenzone and titanium dioxide were 8.93% and 2.07%. The viscosity and adhesiveness were not siginifically different, while cream spreadability was significally different during 4 weeks storage. Testing activity in vivo sunscreen cream o / w combination of oxybenzone and titanium dioxide produced SPF 12.